2012
DOI: 10.5402/2012/682474
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Host Plants on Herbivore Community Composition on Brassica Crops in Western Siberia

Abstract: Experiments on three varieties of Brassica oleracea (white cabbage, red cabbage, and cauliflower) were conducted during the years 2008-2011 in Western Siberia (Russia) to study the influence of host plant on herbivore infestation. The results revealed the evidence of different infestation of white cabbage, red cabbage, and cauliflower by the common herbivores in Western Siberia. Flea beetles as the earliest herbivores preferred to infest white cabbage. Contrary to those herbivores, M. brassicae and P. xylostel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…While highest pupal weight recorded on kale (440 mg), followed by podarok (390 mg), red cabbage (376 mg), cauliflower (374 mg), rutabaga (349 mg), Brussel sprouts (347 mg), nasturtium (345 mg) and horse-radish (332 mg) [8]. While maximum pupal weight of P. brassicae recorded on white cabbage (319.7 mg), followed by cauliflower (303.7 mg) and red cabbage (272.8 mg) [15]. Moreover, P. brassicae pupal weight is directly dependent on reserves stored at the larval stage and pupae with small weight appear when growing conditions at the larval stage were unfavorable [7].…”
Section: Resultsmentioning
confidence: 99%
“…While highest pupal weight recorded on kale (440 mg), followed by podarok (390 mg), red cabbage (376 mg), cauliflower (374 mg), rutabaga (349 mg), Brussel sprouts (347 mg), nasturtium (345 mg) and horse-radish (332 mg) [8]. While maximum pupal weight of P. brassicae recorded on white cabbage (319.7 mg), followed by cauliflower (303.7 mg) and red cabbage (272.8 mg) [15]. Moreover, P. brassicae pupal weight is directly dependent on reserves stored at the larval stage and pupae with small weight appear when growing conditions at the larval stage were unfavorable [7].…”
Section: Resultsmentioning
confidence: 99%
“…Of the biotic factors, the host plant has a significant influence on the dynamics of the pest population. The past research carried out in the Commonwealth of Independent States (CIS) countries revealed that the feed sources like species (Schuler et al, 2003;Chandrashekar et al, 2005;Harvey et al, 2007;Gols et al, 2008;Shternshis et al, 2012;Andreeva et al, 2013;Popova and Hoang, 2015;Fathipour et al, 2019), and their cultivars (Saeed et al, 2010;Soufbaf et al, 2010;Askarianzadeh et al, 2013) affected the survival and abundance of diamondback moth.…”
Section: Introductionmentioning
confidence: 99%
“…According to the monitoring of the phytosanitary control services of Russia, recent years revealed the destructiveness of the diamondback moth has enhanced, with this phytophagous considered one of the dangerous pests of cruciferous crops in Russia (Andreeva and Shatalova, 2017). However, in Russia, the higher abundance of diamondback moth recordings was during the years 1998, 2000 (Ovchinnikova, 2002), 2002, 2008, and 2009(Shternshis et al, 2012Andreeva et al, 2013). The outbreaks of diamondback moth emergence in different regions of Russia also recurred in 2007, 2013, 2015(Shpanev, 2015Poddubnaya, 2016;Andreeva and Shatalova, 2017).…”
Section: Introductionmentioning
confidence: 99%